Efecto de la aplicación de diferentes niveles de abono Biol en la rehabilitación de pasturas naturales del potrero 6 “La Estación”, Quinta Experimental Punzara-UNL - Ponce Chavez, Bryan Sisney (2025)
The objective of this research was to demonstrate the effect of organic fertilizer biol in its different percentages on the chemical characteristics of the soil and on the nutritional values of the natural pastures of paddock number 6 “La Estación” of the Punzara Experimental Farm in the province of Loja. In which an experimental design of completely randomized blocks was used, 7,245.89 m² were used, dividing it into three equal blocks, each block had two divisions, one control and one treatment (T1: 3/17; T2: 5/15; T3: 7/13) with three replications, the same that was carried out in two phases: field and laboratory. The botanical composition in the three blocks showed the presence of the following species among grasses and legumes: common couch grass (Cynodon dactylon), ray grass (Lolium perenne), Kikuyo (Pennisetum clandestinum), white clover (Trifolium repens), and the lesser plantain (Plantago lanceolata). The best results in terms of plant height were for ray grass (lolium perenne) with a pre-treatment height of 32.33 cm and post-treatment reaching 45.33 cm and the lesser plantain (plantago lanceolata) with a control height of 11.00 cm and reaching 21.33 cm after treatment. In the number of leaves there was no significance for any forage species. With respect to nutritional values, significance was obtained for elements for moisture (P= 0.006) and for dry matter with a (P= 0.006), and no significance was obtained for elements for moisture (P= 0.006), and for dry matter with a (P= 0.006).